FASCIATED MUTANT INDUCED BY THE COMBINED TREATMENT OF GAMMA RAYS AND SODIUM AZIDE (20 KR + 0.10% SA) IN LINUM USITATISSIMUM L. - ALKA,; M.Y.K. ANSARI, (International Journal of Pharma and Bio Sciences, 2013)
The present investigation provides the effect of combined treatment of gamma rays and SA (Sodium Azide) on the morphology of Linum usitatissimum. Fasciated plants were obtained in M2 and M3 generation. Various widened and ï¬‚attened organs were found such as fasciated stems, abnormal branches arising from fasciated stems, broad and abnormal leaves. The enhanced activity of apical meristem and cambium resulted in a signiï¬cantly increased circumference of the stem resulting into increasing number of leaves, buds, flowers, fruits and seeds. Moreover the size of fruits and seeds were much bigger than control.